2016
DOI: 10.1038/ncomms13680
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the spin–vibronic coupling mechanism of thermally activated delayed fluorescence

Abstract: Knowing the underlying photophysics of thermally activated delayed fluorescence (TADF) allows proper design of high efficiency organic light-emitting diodes. We have proposed a model to describe reverse intersystem crossing (rISC) in donor–acceptor charge transfer molecules, where spin–orbit coupling between singlet and triplet states is mediated by one of the local triplet states of the donor (or acceptor). This second order, vibronically coupled mechanism describes the basic photophysics of TADF. Through a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
807
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 849 publications
(842 citation statements)
references
References 43 publications
33
807
0
2
Order By: Relevance
“…We have shown that DF reaches a resonant maximum at the point when the CT- 3 LE gap approaches zero, verifying the second-order spin-vibronic mechanism in this system7. The fits of the emission decay curves at different temperatures show that the prompt 1 CT eq lifetime also follows the resonant behaviour, reaching the longest lifetime of 47 ns at the CT- 3 LE zero gap point.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…We have shown that DF reaches a resonant maximum at the point when the CT- 3 LE gap approaches zero, verifying the second-order spin-vibronic mechanism in this system7. The fits of the emission decay curves at different temperatures show that the prompt 1 CT eq lifetime also follows the resonant behaviour, reaching the longest lifetime of 47 ns at the CT- 3 LE zero gap point.…”
Section: Resultssupporting
confidence: 72%
“…( c ) Energy positions of the 1 CT and 3 LE states for the molecules 2,8-DPTZ-DBTO 2 (LHS) and 3,7-DPTZ-DBTO 2 (RHS). Changing from MCH to toluene for 2,8-DPTZ-DBTO 2 moves from type II–III TADF, whereas the equatorial conformer D–A pair (eq)3,7-DPTZ-DBTO 2 is type III in MCH and remains so in toluene (see Etherington et al 7. for notation).…”
Section: Figurementioning
confidence: 99%
“…Previous studies suggested that the ISC and RISC processes due to spin−orbit coupling between pure singlet and triplet charge transfer states is forbidden. 5,47,56,57 However, in the case of intermolecular exciplexes, where negligible energy gap between 1 CT and 3 CT is achieved, hyperfine interactions might become predominant and originate RISC with negligible loss, as no low energy triplet exists below the CT states.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The character of this CT-3 (π-π*) mixture also evolves slightly over its lifetime, which we speculate could be attributed to relaxation of the low-energy vibrational modes coupling the two potential energy surfaces. 34 At no point do we identify a pure, diabatic triplet or CT configuration, but these may be transiently populated, indicating the conventional picture of RISC may not be as simple as suggested. 33,[35][36] It is this mixing with intermediate CT states which enables RISC to occur: the CT component of CT-3 (π-π*) enables a relatively fast (thermally activated) spin flip, resulting in a 1 CT configuration which in turn can emit via mixing with the 1 (π-π*) state.…”
Section: Discussionmentioning
confidence: 99%